Tingkat Pengetahuan Bidan Tentang Imunisasi Dengan Perilaku Pengelolaan Vaksin - Agus Ruhari; Dyah Suryani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: The quality of immunization is closely associated with how the handling and management of such vaccine cold chain maintenance, sterilization equipment and means of immunization immunization. Handling and improper management will no longer cause a potential vaccine to create immunity in infants, but if granted would still result in large losses.Objective: This study aims to determine the relationship of the level of knowledge about the behavior of midwives in immunization with vaccine management in Private Practice Midwives (CPM) in the region Sewon BantulMethods: The study was observational analytic cross sectional approach. The population in this study is the Private Practice Midwives (CPM) serving immunization in practice in the District of Sewon. Samples were taken by purposive sampling techniques, and obtained a number of samples with 50 samples. Data was analyzed using Chi Square statistical analysis.Results: The results showed that there is a significant relationship between the level of knowledge about the behavior of midwives in immunization with vaccine management in Private Practice Midwives (CPM) in the District of Sewon Bantul region indicated by the value of P = 0.000 , RP 15.167Conclusion: There is a relationship between the level of knowledge about the behavior of midwives in immunization with vaccine management in Private Practice Midwives (CPM) in the region Sewon BantulKeywords : Knowledge Level; Immunization; Behavior Management Vaccine